2006
DOI: 10.1097/01.pai.0000153723.59272.02
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Detection in Large Cell Carcinoma of the Lung

Abstract: Large cell carcinomas of the lung are undifferentiated malignant epithelial tumors that lack cytologic features of small cell carcinoma, glandular cell carcinoma, or squamous cell differentiation. Lung surfactant protein A (SP-A) is produced by alveolar type II cells and Clara cells. Most bronchioloalveolar carcinomas of the lung react positively for SP-A. Positive SP-A staining of large cell carcinoma of the lung could indicate that at least part of these tumors have the same cellular origin or differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Also noted was the presence of entrapped non-neoplastic pneumocytes that stained for TTF-1, a reaction that can be misinterpreted as positivity in the tumor cells. The lack of surfactant in most of our cases parallels the findings of Uzaslan et al [19], who reported that only tumors with alveolar type 2 and/or Clara cell-type features are surfactant positive. This association strengthens the finding of lack of immunoreactivity with TTF-1, noted in the most tumors included in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Also noted was the presence of entrapped non-neoplastic pneumocytes that stained for TTF-1, a reaction that can be misinterpreted as positivity in the tumor cells. The lack of surfactant in most of our cases parallels the findings of Uzaslan et al [19], who reported that only tumors with alveolar type 2 and/or Clara cell-type features are surfactant positive. This association strengthens the finding of lack of immunoreactivity with TTF-1, noted in the most tumors included in the current study.…”
Section: Discussionsupporting
confidence: 90%